2015
DOI: 10.1117/1.jbo.20.9.096007
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the progression from intraductal carcinoma to invasive ductal carcinoma based on multiphoton microscopy

Abstract: Intraductal carcinoma is a precancerous lesion of the breast and the immediate precursor of invasive ductal carcinoma. Multiphoton microscopy (MPM) was used to monitor the progression from intraductal carcinoma to invasive ductal carcinoma, which can improve early detection of precursor lesions and halt progression to invasive neoplastic disease. It was found that MPM has the capability to reveal the qualitative changes in features of cells, structure of basement membranes, and architecture of collagens during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Indeed, invasive cancers often show a stromal desmoplastic reaction, a fibrotic condition characterized by increased synthesis and the altered organization of the collagen network, which is associated with a poor prognosis [ 20 , 21 ]. In this regard, we observed that the 3D CRC Day0 µTs saw a drastic reduction in collagen fibers, as reported in the in vivo studies [ 22 ], which is different from the 3D CRC Day4 µTs. The latter presented increased collagen fiber assembly, probably due to the presence of a neosynthetized ECM before the seeding of the HCT-116 cells that allow the TME complexity and uniform spatial cellular distribution to be reproduced, as shown in solid tumors in vivo [ 23 ].…”
Section: Discussionsupporting
confidence: 54%
“…Indeed, invasive cancers often show a stromal desmoplastic reaction, a fibrotic condition characterized by increased synthesis and the altered organization of the collagen network, which is associated with a poor prognosis [ 20 , 21 ]. In this regard, we observed that the 3D CRC Day0 µTs saw a drastic reduction in collagen fibers, as reported in the in vivo studies [ 22 ], which is different from the 3D CRC Day4 µTs. The latter presented increased collagen fiber assembly, probably due to the presence of a neosynthetized ECM before the seeding of the HCT-116 cells that allow the TME complexity and uniform spatial cellular distribution to be reproduced, as shown in solid tumors in vivo [ 23 ].…”
Section: Discussionsupporting
confidence: 54%
“…Our results illustrated that hsa_circ_0006220 may be correlated with lymph node metastasis. Intraductal carcinoma is a precancerous lesion of invasive ductal carcinoma and can develop into invasive ductal carcinoma, which exhibits higher malignancy (27). Our results showed that hsa_ circ_0006220 might indicate the degree of malignancy in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 71%
“…However, early IDC patients did not have typical clinical symptoms and signs, and it was difficult to detect them during normal times. The diagnosis needed to be made based on imaging and pathology examinations, which easily missed the optimal treatment period and posed a serious threat to women's health [ 15 , 16 ]. Therefore, early diagnosis and treatment of IDC are very important.…”
Section: Discussionmentioning
confidence: 99%